Modelling the erosion of electron beam physical vapour deposited thermal barrier coatings - Wellman , Richard (Cranfield University, 2001)
Since the introduction of electron beam (EB) physical vapour deposition (PVD) thermal barrier coatings (TBCs) and their application to moving components in the hot gas stream, erosion has become a prime concern. EB PVD TBCs, due to their unique columnar microstructure are far more strain tolerant than their plasma sprayed (PS) counter parts and can thus be used under more exacting operating conditions. It is under these operating conditions that erosion of the coated components is of primary importance. The main aim of this project was the development of a computer model capable of predicting the erosion rate of EB PVD TBCs under various different conditions. I order to do this it was first necessary to determine the erosion mechanisms of EB PVD TBCs as well as their mechanical properties. Steady state erosion and single impact studies together with SEM were used to determine the erosion mechanisms, while nano indentation techniques were used to obtain the hardness and the Youngs Modulus of the EB PVD TBC. Literature searches contributed to the understanding of erosion principles and factors affecting erosion. All these findings were then used in the development of a Monte-Carlo type computational erosion model capable of predicting the erosive wear rate of EB PVD TBCs under various conditions. The model which has been developed' is capable of predicting the erosion rate of EB PVD TBC to within 30%, so long as the erosion falls within a certain defined mechanism, which can easily be checked against a erosion map, which has been drawn.